2011
DOI: 10.1063/1.3664126
|View full text |Cite
|
Sign up to set email alerts
|

A data-integrated method for analyzing stochastic biochemical networks

Abstract: Variability and fluctuations among genetically identical cells under uniform experimental conditions stem from the stochastic nature of biochemical reactions. Understanding network function for endogenous biological systems or designing robust synthetic genetic circuits requires accounting for and analyzing this variability. Stochasticity in biological networks is usually represented using a continuous-time discrete-state Markov formalism, where the chemical master equation (CME) and its kinetic Monte Carlo eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It turns out that the nonlinear product term ms in (43) makes computations non-trivial due to unclosed moment dynamics -the time evolution of the lower-order moments always depends on high-order moments. Moving forward, one general approach is to exploit closure schemes that approximate higher-order moments as nonlinear functions of lower-order moments [21]- [35]. Here we use an alternative approach based on linearizing the nonlinearity…”
Section: B Dynamic Noise Rejection By Sgfflsmentioning
confidence: 99%
“…It turns out that the nonlinear product term ms in (43) makes computations non-trivial due to unclosed moment dynamics -the time evolution of the lower-order moments always depends on high-order moments. Moving forward, one general approach is to exploit closure schemes that approximate higher-order moments as nonlinear functions of lower-order moments [21]- [35]. Here we use an alternative approach based on linearizing the nonlinearity…”
Section: B Dynamic Noise Rejection By Sgfflsmentioning
confidence: 99%
“…Several other approaches have been previously evaluated. Chevalier and El-Samad, 38 for example, approximated higher order moments using experimental data. Azunre et al 39 showed that for very small molecule numbers, using only two moments can lead to unstable results.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR or flow cytometry assays [4, 21]. Although this particular problem has been discussed extensively in the computational biology and statistical literature ([9, 12] and references therein), its asymptotic analysis was often dismissed due to a small number of longitudinal data points available from typical laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%